Investigation of Transformation in the Amorphous Phase of Polyaramid as a Result of Heat Treatment - Mamajanova Rashida Tukhtaevna (Zien Journals, 2022)
This article examined how polyacrylamide changes under the influence of temperature. As a result of this, the conclusions of the results of the formation of the amorphous phase and its application in several ways are given
Keywords: Nitroxyl radicals; EPR; tetramethylpiperidine; PKA